13. EVALUATION OF SURGICAL OUTCOMES FOR THE TREATMENT OF MIDSHAFT HUMERAL FRACTURES USING LOCKING PLATE FIXATION AT VINH CITY GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objective: To evaluate the surgical outcomes of treating midshaft clavicle fractures with locking plate fixation at Vinh City General Hospital. Subjects and methods: This descriptive study (retrospective and prospective) included 54 patients with mid-shaft humeral fractures who underwent surgery at Vinh City General Hospital from January 2021 to April 2023. Results: 92.6% of patients achieved anatomical alignment, with no cases of residual displacement after reduction. Primary wound healing was observed in 98.1% of cases, while 1.9% experienced surgical site infection. Union of the fracture was achieved in 98% of patients, with a union rate of 85.7% and a poor union rate of 12.3%. Nonunion occurred in 2% of cases. No intraoperative complications were reported, and 87.7% of patients showed good functional recovery of shoulder joint mobility based on the Constant-Murley scoring system. Overall, 85.8% of patients had favorable outcomes. Conclusion: Surgical treatment of midshaft clavicle fractures with locking plate fixation resulted in a high rate of anatomical alignment, good wound healing, satisfactory union of the fracture in the majority of patients, favorable shoulder joint function, and overall good outcomes with few complications.
Keywords: Humeral fractures, locking plate fixation, outcomes.